El trono de fuego : novela grafica - Collar, Orpheus (Barcelona : Montena, 2019)
Ever since the gods of Ancient Egypt were unleashed in the modern world, Carter Kane and his sister, Sadie, have been in trouble. As descendants of the House of Life, the Kanes have some powers at their command; but the devious gods haven't given them time to master their skills at Brooklyn House, a training ground for young magicians. And now their most threatening enemy yet--the Chaos snake, Apophis--is rising. If they don't prevent him from breaking free in a few days' time, the world will end. In other words, it's a typical week for the Kane family. To have any chance of battling the forces of Chaos, the Kanes must revive the sun god, Ra. But that would be a feat more difficult than any magician has ever accomplished. First they have to search the world for the Book of Ra, then they have to learn how to chant its spells. Oh, and did we mention that no one knows where Ra is, exactly? Narrated by two different wisecracking voices, featuring a large cast of new and unforgettable characters, and with adventures spanning the globe, this second installment of the Kane Chronicles is nothing short of a thrill ride.
10-14
Keywords: Siblings -- Comic books, strips, etc. -- Juvenile fiction -- Spanish language materials; Magic -- Comic books, strips, etc. -- Juvenile fiction -- Spanish language materials; Brothers and sisters -- Fiction; Magic -- Fiction; Spanish language materials; Hermanos -- Libros de caricaturas, tiras comicas, etc. -- Novela juvenil; Magia -- Libros de caricaturas, tiras comicas, etc. -- Novela juvenil; Siblings; Magic; Novelas graficas; Graphic novels; Graphic novels